The Separation of Cannabinoids on Sub-2 µm Immobilized Polysaccharide Chiral Stationary Phases - Takafumi Onishi; Weston J. Umstead (MDPI AG, 2021)
The increased use and applicability of Cannabis and Cannabis-derived products has skyrocketed over the last 5 years. With more and more governing bodies moving toward medical and recreational legalization, the need for robust and reliable analytical testing methods is also growing. While many stationary phases and methods have been developed for this sort of analysis, chiral stationary phases (CSPs) are unique in this area; not only can they serve their traditional chiral separation role, but they can also be used to perform achiral separations. Given that mixtures of cannabinoids routinely contain enantiomers, diastereomers, and structural isomers, this offers an advantage over the strictly achiral-only analyses. This work presents the separation of a 10-cannabinoid mixture on several polysaccharide-based sub-2 µm CSPs with both normal-phase and reversed-phase ultra-high-performance liquid chromatography (UHPLC) conditions. Along with the separation of the mixture, appropriate single-peak identification was performed to determine the elution order and reported where applicable.